INTEGRATION OF ENTERPRISE RISK MANAGEMENT IN STRATEGIC PLANNING TO ACHIEVE HIGH-QUALITY GROWTH: A CASE STUDY OF PT PLN NUSANTARA POWER - Rio Afrianda (INJOSEDU: International Journal of Social and Education, 2026)
The global energy industry is facing a major transformation due to sustainability demands and the green energy transition. This study aims to analyze the integration of Enterprise Risk Management (ERM) into strategic planning at PT PLN Nusantara Power (PLN NP) to achieve High-Quality Growth. Using a descriptive qualitative approach with a case study method on the 2024 Annual Report, this research explores how risk management mechanisms have transformed from a mere compliance function into a strategic enabler. The findings show that PLN NP successfully integrated ERM through three main pillars: alignment of risk appetite with Key Performance Indicators (KPIs), strengthening the Governance, Risk Management, and Compliance (GRC) framework, and utilizing digitalization (iCORE and Remool) for operational risk mitigation. Data analysis results indicate a decrease in the Equivalent Forced Outage Rate (EFOR) and the achievement of a KPI score of 106.31, confirming that risk integration strengthens organizational resilience amidst the uncertainties of the energy transition. Theoretically, this research reinforces the relevance of the Resource-Based View (RBV) and Contingency Theory in positioning ERM as a strategic capability that creates sustainable competitive advantage.